K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

11 tháng 12 2017

Thực hiện phép chia :

x + ax +b x - x - 1 x + x + (a + 2) x - x - x x + (a+1)x x - x - x (a+2)x +x (a+2)x - (a+2)x - (a+2) (a + 3)x+(a+b+2) 4 4 3 3 3 2 2 2 2 2 2 2 2

Vậy để \(x^4+ax^2+b⋮\left(x^2-x-1\right)\) thì \(\left(a+3\right)x+\left(a+b+2\right)=0\)

\(\Leftrightarrow\hept{\begin{cases}a+3=0\\a+b+2=0\end{cases}}\Leftrightarrow\hept{\begin{cases}a=-3\\b=1\end{cases}}\)

Vậy a = -3, b - 1.

a: \(\Leftrightarrow10x^2-15x+8x-12+a+12⋮2x-3\)

=>a+12=0

hay a=-12

b: \(\Leftrightarrow2x^2+8x+\left(a-8\right)x+4a-32-4a+28⋮x+4\)

=>-4a+28=0

=>a=7

c: \(\Leftrightarrow2x^3-2x-x^2+1+\left(a+2\right)x+b-1⋮x^2-1\)

=>a+2=0 và b-1=0

=>a=-2 và b=1